Kajian terhadap tahap kecekapan syarikat insuran hayat am menggunakan analisis perbatasan stokastik (APS) - Zaidi Isa,; Roziana Baharudin, (Penerbit ukm, 2007)

(untitled)
This paper focuses on the stochastic production frontier analysis (SFA) approach in an attempt to measure the relative efficiency of life and general insurance industry in Malaysia for the years 2003 and 2004 by employing the Battese and Coelli invariant efficiency model. The results of the analysis show that on average, companies from both sectors are technically inefficient although there are a few companies that manage to record a good efficiency score. Besides that, unlike companies in general insurance, the level of efficiency scores for life insurance companies do not vary across time. The level of efficiency scores for general insurance companies on average increases in the year 2004 relatively to the year 2003